Corporate governance practices and sustainability reporting quality: evidence from the Nigerian listed financial institution - Ezekiel Oluwagbemiga Oyerogba; Femi Oladele; Peace Ebunlomo Kolawole; Mofoluwake Adedamola Adeyemo (Cogent Business & Management, 2024)
This study ascertains whether a composite corporate governance (CCG) index is related to the sustainability reporting quality of listed banks in Nigeria. We posit that, for a company to report adequately on sustainability initiatives, there must be a strong corporate governance mechanism. Using a balanced set of panel data with 190 observations from 19 quoted banks for a period of ten years (2012–2021), this study investigates the relationship between the corporate governance index and sustainability reporting quality. Categorical data were obtained using a scale of 0–6 and dichotomous data were obtained using a binary dummy. Our results show that corporate governance mechanisms have a statistically significant influence on the quality of sustainability reporting. We establish that banks with diluted ownership, greater board independence, a high level of audit committee financial expertise, and greater shareholder rights and protection are likely to have higher SRQ. Our results provide empirical support for resource-based theory which emphasizes the internal capabilities of a firm as a source of competitive advantage. In this context, effective CG can be a strategic resource that will help position the firm for sustainable performance. This study highlights the corporate governance mechanisms that banks should focus on towards achieve quality sustainability reporting, which includes diluted ownership, board independence, financial expertise in the audit committee, board diversity, shareholders' rights, and protection. In addition, it establishes that adequate sustainability practices enhance stakeholders' confidence in the performance of listed companies.
Keywords: 650; Board independence; shareholders right and protection; diluted ownership; return on capital employed; audit quality